STUDI KORELASI KELINCAHAN, KECEPATAN DAN MOTIVASI LATIHAN TERHADAP KEMAMPUAN MENGGIRING BOLA FUTSAL PADA UNIT KEGIATAN MAHASISWA FUTSAL STKIP PASUNDAN CIMAHI - Gunawan, Gugun (STKIP Pasundan, 2015)
The purpose of this study is to know the correlation of agility, speed and motivation of training on the ability to dribble futsal in the futsal student unit STKIP Pasundan Cimahi. The study was conducted on 28 research samples using the correlation method. To collect data the author uses tests and questionnaires. Tests carried out to measure agility are circuit training, tests to measure speed are 20 meters running and tests to measure dribbling skills are boomerang tests. The results of this study are: First, there is a positive and significant correlation of agility to the ability of dribbling with a correlation coefficient of 0.67 and a large index of determination of 44.89%. Second, there is a positive and significant correlation of agility to the ability to dribble with a correlation coefficient of 0.484 and a large index of determination of 23.43%. Third, there is a positive and significant correlation of agility to the ability to dribble with a correlation coefficient of 0.398 and a large index of determination of 15.84%. Fourth, there is a positive and significant correlation together from the variable of agility, speed and ability to dribble with a correlation coefficient of 0.517 and a large index of determination of 28.05%. From the results of data analisys it can be concluded that to improve the ability of dribbling can be done physically by practicing student agility and speed while psychologically by increasing motivation to practice. There are still other variables that also influence the ability to dribble apart from the variables mentioned above but escape the research process. Therfore it needs to be done further by expanding the scope of the research discussion